Evidence for Rise in Meningococcal Serogroup C Bactericidal Antibody Titers in the Absence of Booster Vaccination in Previously Vaccinated Children. Issue 3 (March 2018) - Badahdah, Al-Mamoon; Khatami, Ameneh; Tashani, Mohamed; Rashid, Harunor; Booy, Robert
Abstract : Background: The introduction of meningococcal serogroup C (MenC) conjugate vaccines in the United Kingdom and Australia led to an impressive decline in the incidence of invasive disease. This study examined bactericidal antibody titers over time in the UK and Australian children who received a MenC conjugate vaccine in early childhood to test the hypothesis that ongoing boosting of immunity in the absence of further doses of vaccine in some children may contribute to ongoing protection from disease. Methods: Serum bactericidal assay using rabbit complement (rSBA) titers at each follow-up visit were compared with all preceding visits to identify any ≥4-fold rise in titers. The proportion of children with a ≥4-fold rise in rSBA titers in paired sera at any visit-to-visit comparison was calculated. Results: Of 392 children with at least one set of paired sera in the Australian cohort, 72 (18.4%) had a ≥4-fold increase in rSBA titers at least one year after vaccination, including six children (1.5%) who showed evidence of boosting twice. Of 234 children with at least one set of paired sera in the UK cohort, 39 (16.7%) had a ≥4-fold rise in rSBA titers at least one year after vaccination including 2 children (0.9%) with evidence of boosting twice. Conclusions: A substantial minority of children immunized with MenC conjugate vaccine in early childhood had a rise in bactericidal antibody titers in the years after immunization in the absence of booster vaccination. This occurs most commonly at around 6–7 years of age corresponding to school entry and greater social mixing and might indicate exposure to MenC carriage.